Engineering of CYP153A33 With Enhanced Ratio of Hydroxylation to Overoxidation Activity in Whole-Cell Biotransformation of Medium-Chain 1-Alkanols - Park, Hyuna; Bak, Doyeong; Jeon, Wooyoung; Jang, Minjung; Ahn, Jung-Oh; Choi, Kwon-Young (Frontiers in Bioengineering and Biotechnology, 2022)
α,ω-Dodecanediol is a versatile material that has been widely used not only as an adhesive and crosslinking reagent, but also as a building block in the pharmaceutical and polymer industries. The biosynthesis of α,ω-dodecanediol from fatty derivatives, such as dodecane and dodecanol, requires an ω-specific hydroxylation step using monooxygenase enzymes. An issue with the whole-cell biotransformation of 1-dodecanol using cytochrome P450 monooxygenase (CYP) with ω-specific hydroxylation activity was the low conversion and production of the over-oxidized product of dodecanoic acid. In this study, CYP153A33 from Marinobacter aquaeolei was engineered to obtain higher ω-specific hydroxylation activity through site-directed mutagenesis. The target residue was mutated to increase flux toward α,ω-dodecanediol synthesis, while reducing the generation of the overoxidation product of dodecanoic acid and α,ω-dodecanedioic acid. Among the evaluated variants, CYP153A33 P136A showed a significant increase in 1-dodecanol conversion, i.e., 71.2% (7.12 mM from 10 mM 1-dodecanol), with an increased hydroxylation to over-oxidation activity ratio, i.e., 32.4. Finally, the applicability of this engineered enzyme for ω-specific hydroxylation against several 1-alkanols, i.e., from C6 to C16, was investigated and discussed based on the structure-activity relationship.